SISTEM INFORMASI PENJUALAN DAN PENGENDALIAN STOCK BARANG BANGUNAN PADA TOKO BANGUNAN DELIMA - Maulana Mustopa; Ifan Junaedi; Anton Zulkarnain Sianipar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Digital sales system is now widely utilized by small and medium businesses so as to facilitate customers in ordering goods moreover the internet becomes the lifestyle of most people who want everything to be practical and fast. Pomegranate Building Shop is a building shop that is developing and engaged in the sale of building materials, where the processing of goods data is still done manually and the entire report of the bookkeeping system activities are still under construction. The obstacles that arise are the problem of time in which in doing bookkeeping or checking the goods data for too long and also the problem of controlling the stock of goods available is less so regularly in a good manner. Therefore the author designed the Web-based Building Materials Stock Information And Control System using the Php Mysql,Xampp and Laravel Framework. The data source obtained is through the primary data source and the data collection technique is done by observation, interview and documentation. It is expected that this system can facilitate pomegranate stores in running their business and gain profits amid a lot of competition.